Pengaruh Kepuasan Kerja, Dan Motivasi Kerja Terhadap Kinerja Karyawan/ti Dengan Komitmen Organisasional Sebagai Variabel Intervening (Studi Karyawan Outsourcing PT. J Yang Ditempatkan Di Kampus II Untar Jakarta). - Muhammad Tony Nawawi (Jurnal Manajemen dan Bisnis Indonesia, 2015)
This study on the Influence Job Satisfaction and Job Motivation on Employee Performance with Organizational Commitment as an Intervening Variable (Study of Employee outsourcing PT J placed Tarumanagara University. Population in this study all employees outsourcing PT J, with sampling techniques is purposive random sampling, and samples taken 50 employees. Purpose of the study is to examine and analyze the effect of job satisfaction and motivation on employee performance. Analysis is the method of multiple regression analysis and test assumptions, and validity testing is also done and reliability with the help of SPSS (Statistical Program for Society Science) versus 16:00. analysis showed that the presence of a significant positive effect between satisfaction and job motivation on organizational commitment, with a significance of 0.000 <0.05, and R Square value 0.308, meaning 30.80% of organizational commitment is influenced by the level of job satisfaction and motivation. while other results indicate that the presence of a significant positive effect between job satisfaction and motivation and organizational commitment to employee performance, with a significance of 0.000 <0.05, and R Square value 0.732 performance of 73.2% means employees outsourcing is influenced by the level of satisfaction, motivation, and organizational commitment.Keywords: job satisfaction, job motivation, employee performance, organizational commitment, hypotheses testing, multiple regression.